Math CentralQuandaries & Queries


Subject: Algebra
Name: Evan
Who are you: Student

How do you write the equation y= 4x-2 in ax+by=c form?

Hi Evan,

I am going to demonstrate with a different example. Suppose that the equation is 2 - 5y = 6x. You want to put it in the form
ax + by = c. The first thing that I notice is that the term with an x in it should be on the left side of the equation and it is on the right. To get it on the left side of the equation add -6x to both sides. The equation then becomes

-6x + 2 -5y = -6x + 6x

But -6x + 6x = 0 so the equation is

-6x + 2 -5y = 0

Now the constant term (the term with no x or y in it) should be on the right so add -2 to each side to get

-2 -6x + 2 -5y = -2

which is

-6x -5y = -2

This is in the form requested but you can neaten it a little by multiplying both sides by -1 to get

6x + 5y = 2


About Math Central


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences.
Quandaries & Queries page Home page University of Regina PIMS